Hyponatremia in Liver Cirrhosis - Jang, Cheolmin; Jung, Young Kul (The Korean journal of gastroenterology, 2018)
Hyponatremia is a commonly observed complication that is related to hypoalbuminemia and portal hypertension in patients with advanced liver cirrhosis. Hyponatremia in patients with liver cirrhosis is mostly dilutional hyponatremia and is defined when the serum sodium concentration is below 130 meq/L. The risk of complications increases significantly in cirrhotic patients with hyponatremia, which includes spontaneous bacterial peritonitis, hepatorenal syndrome, and hepatic encephalopathy. In addition, hyponatremia is associated with increased morbidity and mortality in patients with cirrhosis, and is an important prognostic factor before and after liver transplantation. The conventional therapies of hyponatremia are albumin infusion, fluid restriction and loop diuretics, but these are frequently ineffective. This review investigates the pathophysiology and various therapeutic modalities, including selective vasopressin receptor antagonists, for the management of hyponatremia in patients with liver cirrhosis.